Epistolae Plenae - Ferreiro, Alberto, compiler.
1 online resource.
Keywords: “This monograph offers a full inventory and analysis of all of the extant correspondence between the bishops of Hispania and Rome from the third to the seventh century. No such study has been executed in any language. The study intends to enlighten the reader on how the bishops of Hispania and the Roman pontiffs interacted with each other. Of interest is the development of the Petrine Primacy and how it was applied in many situations where Rome was asked to intervene in Hispania, dealing with issues including the liturgy, creeds, heresy, sacraments, episcopal authority, ecclesiology, papal authority and more“.